The Impact of Abusive Supervision on Nurses’ Organizational Silence: The Multiple Linear Mediation of Psychological Capital and Fear - Liang Y; Zhang Y; Feng Y; Huang Y; Zhang C (Journal of Multidisciplinary Healthcare)
Yali Liang,1,* Yunxin Zhang,1,* Yong Feng,2 Yuying Huang,2 Cuiling Zhang1 1Nursing Department, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 2College of Nursing, Shanxi University of Chinese Medicine, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cuiling Zhang, Nursing Department, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, NO. 99, Longcheng Street, Xiaodian District, Taiyuan, 030032, People’s Republic of China, Tel +86-13753482546, Email sxbqezcl@163.comPurpose: To assess abusive supervision and organizational silence among nurses and investigate the mediating influence of psychological capital and fear.Background: Since the end of 2019, China’s National Development and Reform Commission (NDRC) department has decided to start the construction of regional medical centers in Shanxi, reducing cross-provincial and cross-regional medical care. In order to improve the overall standard of care in a hospital in a short period of time, health care leadership decision makers may adopt various effective leadership management practices to achieve the set goals and have high work pressure at the same time. In this case, abusive management may occur.Methods: A cross-sectional survey design was employed. In January -March 2024, a convenience sampling method was used to collect data from 470 nurses in a total of 5 hospitals in Shanxi province they were required to complete the questionnaires online anonymously. The chain mediation model was tested using the PROCESS macro program in the SPSS software and multiple linear regression model was used to verify the mediating effect.Results: Psychological capital and fear mediate the relationship between abusive supervision and nurses’ organizational silence, playing indirect mediating roles. Abusive supervision was positively associated with nurses’ organizational silence. Additionally, psychological capital plays a negative mediating role, accounting for 48.48% of the indirect effect, and fear plays a positive mediating role, accounting for 45.83% of the indirect effect. They form a chain intermediary, accounting for 5.69% of the indirect effect.Conclusion: Psychological capital and fear mediate the impact of abusive supervision on nurses’ organizational silence. Positive leadership training should be conducted to help reducing the level of head nurses’ abusive supervision behaviors, while also fostering actions that elevate nurses’ psychological capital levels.Keywords: Abusive supervision, Nurses’ organizational silence, psychological capital, fear, mediating effect